2015
DOI: 10.1039/c4ta04633a
|View full text |Cite
|
Sign up to set email alerts
|

Shortened aerogel fabrication times using an ethanol–water azeotrope as a gelation and drying solvent

Abstract: Native and cross-linked aerogel monoliths were fabricated in a few hours using a technique that does not require solvent exchange prior to supercritical drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…For these applications, a modulus of hundreds of MPa and an energy absorption of tens of J g À1 are required. In our previous work, we showed that the modulus of the composites could be increased by several times when the functionality of the cross-linking monomer was increased [4]. This result was in agreement with general trends of polymer chemistry, which show that the modulus of composites increases with the functionality of the cross-linker [5,7e9].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…For these applications, a modulus of hundreds of MPa and an energy absorption of tens of J g À1 are required. In our previous work, we showed that the modulus of the composites could be increased by several times when the functionality of the cross-linking monomer was increased [4]. This result was in agreement with general trends of polymer chemistry, which show that the modulus of composites increases with the functionality of the cross-linker [5,7e9].…”
Section: Introductionsupporting
confidence: 88%
“…In these methods, aerogels are prepared using one-pot chemistry and dried using supercritical organic solvents. In previous work done by our group, native silica and crosslinked aerogels were produced in a matter of hours without requiring solvent exchange [4]. The composites fabricated with our method had Young's moduli on the order of a few tens of MPa.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Meador et al [128] introduced epoxy monomer in the initial sol, Wingfield et al [129] used an acrylic monomer and Duan et al [130] used a custom-synthesized, water-dispersible urethane oligomer. Recently, White [131] shortened the aerogel composite fabrication by conducting the experiment with simple one pot approach and using the more economic-friendly ethanol-water azeotrope mixture as gelation solvent.…”
Section: Accepted Manuscriptmentioning
confidence: 99%